2016
DOI: 10.1515/biol-2016-0006
|View full text |Cite
|
Sign up to set email alerts
|

MafB, a target of microRNA-155, regulates dendritic cell maturation

Abstract: MafB is a member of bZip transcription factors that share similar basic region/leucine zipper DNA binding motifs and N-terminal activation domains. It is well known that MafB is highly expressed in macrophages and promotes differentiation of myeloid progenitors into macrophage. However, little is known about its function in dendritic cells. Here, we report that MafB, as a target of miR-155, which had been reported to be required for dendritic cell maturation and function, regulated dendritic cell maturation. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 30 publications
(25 reference statements)
0
4
0
Order By: Relevance
“… 42 Evidence of impaired cDC maturation was suggested by upregulation of ID1 , which antagonizes dendritic cell differentiation and antitumor immunity in mice, 43 as well as increased MAFB transcription, which suppresses cDC maturation. 44 cDCs from cases also demonstrated decreased expression of FOSB and many MHC II genes. 45 pDCs in cases also showed markers of immune activation, including upregulation of RELB , which promotes DC activation through RelB-p50 dimer, 46 upregulation of MHC class I and class II genes, and unfolded protein response activation, as shown by increased transcription of XBP1 47 (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 96%
“… 42 Evidence of impaired cDC maturation was suggested by upregulation of ID1 , which antagonizes dendritic cell differentiation and antitumor immunity in mice, 43 as well as increased MAFB transcription, which suppresses cDC maturation. 44 cDCs from cases also demonstrated decreased expression of FOSB and many MHC II genes. 45 pDCs in cases also showed markers of immune activation, including upregulation of RELB , which promotes DC activation through RelB-p50 dimer, 46 upregulation of MHC class I and class II genes, and unfolded protein response activation, as shown by increased transcription of XBP1 47 (Supplemental Fig.…”
Section: Resultsmentioning
confidence: 96%
“…In recent years, with the continuous development of the whole gene sequencing and restriction fragment length polymorphism (RFLP) study, the genome-wide association studies (GWAS) based on single nucleotide polymorphism (SNP) chip technology provided a great progress for the study of pathogenesis of primary hypertension (Wellcome Trust Case Control Consortium, 2007, Levy et al, 2007). A large number of GWAS reported several hypertension susceptibility gene in primary hypertension patients from Europe, China, Japan and Korea, which laid the foundation for the study of the pathogenesis of hypertension (Hong et al, 2009, Ehret et al, 2008, Maruthamuthu and Kandasamy, 2016, Yang et al, 2016, Zhu et al, 2011). FGF5 is one of the fibroblast growth factors and the existing studies showed that it played an important role in the control of the animal hair growth process (Higgins et al, 2014, Kubelkova and Macela, 2015, Haitham, 2016, Chen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…2E) 38 . Evidence of impaired cDC maturation was suggested by upregulation of ID1, which antagonizes dendritic cell differentiation and antitumor immunity in mice 39 , as well as increased MAFB transcription, which suppresses cDC maturation 40 . cDCs from cases also demonstrated decreased expression of FOSB and many MHC II genes 41 .…”
Section: Resultsmentioning
confidence: 99%